The synthesis of 2, 3, 6-trisubstituted 1-oxo-1, 2-dihydroisoquinolines as potent CRTh2 antagonists. Issue 23 (1st December 2017) - Huang, Xianhai; Rao, Ashwin; Zhou, Wei; Aslanian, Robert; Nargund, Ravi; Buevich, Alexei; Zhang, Li-Kang; Qiu, Hongchen; Yang, Xiaoxin; Garlisi, Charles G.; Correll, Craig; Palani, Anandan
Graphical abstract: Abstract: New synthetic methods were developed for the preparation of 2, 3, 6-trisubstituted 1-oxo-1, 2-dihydroisoquinolines as CRTh2 antagonists. The isoquinolinone core could be constructed before the introduction of substitution groups or synthesized through a catalytic intramolecular cyclization reaction with desired substitution groups properly installed. These synthetic strategies have helped to accelerate the SAR development of this series, and potent lead compounds were identified in both the CRTh2 receptor binding assay and the CD11b biomarker assay.